Rubber composition and method for producing same

The integration of mechanically treated cellulose nanofibers with chloroprene rubber through a specific mixing and drying process enhances tensile stress and reduces strain in chloroprene rubber compositions, addressing the limitations of conventional reinforcing materials.

JP7654960B2Active Publication Date: 2025-04-02TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020190440
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-19
Filing Date
2020-11-16
Publication Date
2025-04-02
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

Chloroprene rubber compositions face limitations in achieving high tensile stress and elasticity while maintaining appropriate hardness due to the reinforcing effects of conventional granular reinforcing materials, and existing methods for incorporating cellulose fibers in chloroprene rubber are costly and inefficient.

Method used

A rubber composition comprising 1.2 to 3.0 parts by weight of cellulose nanofibers per 100 parts by weight of chloroprene rubber, where the cellulose nanofibers are defibrated only by mechanical treatment and mixed with chloroprene rubber latex, followed by freezing, coagulation, and freeze-drying to enhance tensile stress and reduce strain.

Benefits of technology

The composition achieves a significant increase in 100% tensile stress with low strain and improved handling properties, with a 1.5 MPa or more increase per part by weight of cellulose nanofiber added, while maintaining manageable hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654960000001
    Figure 0007654960000001
Patent Text Reader

Abstract

To provide a rubber composition excellent in elasticity and low loss property and to provide a method for producing the rubber composition.SOLUTION: As the rubber composition is used a rubber composition including 1.2 to 3.0 pts.wt. of cellulose nanofibers based on 100 pts.wt. of chloroprene rubber in which the increase width of 100% tensile stress (M100) of a vulcanized sheet formed by vulcanizing the rubber composition is 1.5 MPa / part by weight or more based on the addition amount of cellulose nanofibers. The increase width of M100 is calculated by subtracting a value of M100 of a vulcanized sheet including no cellulose nanofibers from a value of M100 of a vulcanized sheet including cellulose nanofibers and then dividing by the amount of cellulose nanofibers included.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition and a method for producing the same. [Background technology]

[0002] Chloroprene rubber is used in a wide range of applications because it has a good balance of physical properties among various synthetic rubbers. Depending on the modification at the end, there are general-purpose mercaptan modifications and sulfur modifications with excellent dynamic properties, the latter of which has better mechanical properties, but in recent years, there has been a demand for even higher elasticity and improved heat resistance due to the increasing demand for higher performance and more severe usage environments.

[0003] Tensile stress is an index of elasticity, and it can be improved by blending reinforcing materials such as carbon black and silica, but the reinforcing effect of these granular reinforcing materials is limited due to their particle size and specific surface area. In addition, the hardness of the vulcanized rubber increases significantly when blending reinforcing materials, which reduces the processability of rubber products, so there is a limit to the reinforcing effect in order to maintain the appropriate hardness of the rubber.

[0004] On the other hand, fiber-shaped reinforcing materials have been proposed, and tires and the like that contain cellulose have been proposed (for example, Patent Document 1). However, hydrophilic cellulose has poor dispersibility compared to hydrophobic rubber, and therefore has a low reinforcing effect. As a countermeasure, tires have been proposed in which nano-order cellulose, a dispersant for dispersing it, and a silane coupling agent for fixing it are compounded in natural rubber latex (for example, Patent Documents 2 and 3). However, these methods require separate agents such as dispersants for dispersing the rubber and cellulose, which increases costs. In addition, little consideration has been given to chloroprene rubber.

[0005] On the other hand, it is known that chloroprene polymers can be obtained by polymerizing chloroprene in an aqueous emulsion containing an emulsifier and an initiator in the presence of an emulsifier. Generally, this polymerization reaction is carried out in the presence of an alkali metal salt of a carboxylic acid in a strong alkaline atmosphere, but since cellulose is hydrolyzed in a strong alkaline environment, little research has been done on chloroprene latex, which is a strong alkali. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-206864 A [Patent Document 2] JP 2009-191197 A [Patent Document 3] JP 2009-191198 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in view of the above problems, and an object of the present invention is to provide a chloroprene rubber composition which exhibits low strain and excellent tensile stress, and a method for producing the same. [Means for solving the problem]

[0008] Under such a background, the present inventors have conducted intensive research to solve the above problems, and have found that a rubber composition containing chloroprene rubber and cellulose nanofibers can be used to exhibit low hardness, low strain, and excellent tensile stress. That is, the respective aspects of the present invention are [1] to [5] shown below. [1] A rubber composition comprising 1.2 to 3.0 parts by weight of cellulose nanofiber per 100 parts by weight of chloroprene rubber, wherein the increase in 100% tensile stress (M100) of a vulcanized sheet obtained by vulcanizing the rubber composition is 1.5 MPa / part by weight or more relative to the amount of cellulose nanofiber added.

[0009] The increase in M100 is calculated by subtracting the M100 value of the vulcanized sheet that does not contain cellulose nanofiber from the M100 value of the vulcanized sheet that contains cellulose nanofiber, and dividing the result by the amount of cellulose nanofiber contained. [2] The rubber composition according to [1] above, characterized in that the surface tension of a 1 wt % aqueous solution of the cellulose nanofibers is 60 mN / m or less. [3] The rubber composition according to [1] or [2] above, wherein the cellulose nanofibers do not contain carboxylates or carboxylic acids and are defibrated only by mechanical treatment. [4] A method for producing a rubber composition according to any one of [1] to [3] above, characterized in that an aqueous dispersion of cellulose nanofibers is mixed with chloroprene rubber latex to obtain a cellulose nanofiber-dispersed rubber latex mixture, the chloroprene rubber is then frozen and coagulated, and further washed with water and dried. [5] The method for producing a rubber composition according to the above [4], wherein the viscosity of the cellulose nanofiber-dispersed rubber latex mixture is 1000 mPa·s or less. Effect of the Invention

[0010] By using the rubber composition of the present invention, it is possible to obtain a vulcanized rubber that exhibits low strain and excellent tensile stress. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below.

[0012] One embodiment of the rubber composition of the present invention contains 1.2 to 3.0 parts by weight of cellulose nanofiber per 100 parts by weight of chloroprene rubber, and the increase in 100% tensile stress (M100) of a vulcanized sheet obtained by vulcanizing the rubber composition is 1.5 MPa / part by weight or more relative to the amount of cellulose nanofiber added.

[0013] Chloroprene rubber can be obtained by emulsion polymerization of chloroprene or chloroprene and a monomer copolymerizable therewith.

[0014] Examples of monomers copolymerizable with chloroprene include 2,3-dichloro-1,3-butadiene, 2-cyano-1,3-butadiene, 1-chloro-1,3-butadiene, 1,3-butadiene, styrene, acrylonitrile, methyl methacrylate, methacrylic acid, acrylic acid, etc., and although it is possible to use one or more of these in combination, this is not necessarily required, and they are used as appropriate depending on the required physical properties. The amount of copolymerizable monomer is not particularly limited, but generally 30 parts by weight or less is used per 100 parts by weight of chloroprene rubber so as not to impair the properties of the chloroprene rubber.

[0015] The chloroprene rubber preferably contains 3 to 7% by weight of either or both of a carboxylic acid and an alkali metal salt of a carboxylic acid. Within this range, the emulsion stability during chloroprene polymerization is excellent, and problems such as poor freezing do not occur when the rubber is extracted from the latex by freeze-drying.

[0016] Examples of the carboxylic acid or alkali metal salt of the carboxylic acid include rosin acid or its alkali metal salt, fatty acid or its alkali metal salt, polycarboxylic acid or its alkali metal salt, etc. Examples of the alkali metal salt include lithium, sodium, potassium, cesium, etc. These may be used alone or in combination of two or more, but from the viewpoints of polymerization stability, cohesiveness during drying, and rubber performance, it is preferable to use an alkali metal salt of rosin acid, and further a potassium salt of rosin acid.

[0017] In the emulsion polymerization of chloroprene rubber, for example, the above-mentioned monomers are mixed with an emulsifier, water, a polymerization initiator, a chain transfer agent, other stabilizers, etc., and polymerization is carried out at a predetermined temperature, and a polymerization terminator is added at a predetermined polymerization conversion rate to terminate the polymerization.

[0018] As the emulsifier, an alkali metal salt of the above-mentioned carboxylic acid can be used.

[0019] The amount of the emulsifier is not particularly limited, but in consideration of the stability of the chloroprene latex obtained after polymerization, it is preferably 3 to 7 parts by weight per 100 parts by weight of the chloroprene rubber.

[0020] As the polymerization initiator, known free radical substances can be used, for example, peroxides such as potassium persulfate and ammonium persulfate, hydrogen peroxide, inorganic or organic peroxides such as tertiary butyl hydroperoxide, etc. These can be used alone or in combination with reducing substances such as thiosulfates, thiosulfites, hydrosulfites, organic amines, etc. in a redox system.

[0021] The polymerization temperature is not particularly limited, but is preferably in the range of 10 to 50°C.

[0022] In the method for producing a rubber composition according to one embodiment of the present invention, the time when polymerization is completed is not particularly limited, but in terms of productivity, polymerization is generally performed until the monomer conversion rate reaches 60% to 95%. If the conversion rate is below 60%, the production amount is small, the solid content of the latex is low, and the cost of drying water becomes high, while if the conversion rate is above 95%, the polymerization time becomes very long.

[0023] The polymerization terminator is not particularly limited as long as it is a commonly used terminator, and examples thereof include phenothiazine, 2,6-t-butyl-4-methylphenol, and hydroxylamine.

[0024] The Mooney viscosity of the raw rubber is not particularly limited as long as it satisfies the high elastic stress of the present invention, but in consideration of kneading workability, it is preferably 20 to 80. The measurement of the Mooney viscosity is started 1 minute after preheating at a temperature of 100°C at an angular velocity of 2 revolutions per minute, and the value is read 4 minutes after the start of the measurement.

[0025] Cellulose nanofibers are cellulose fibers contained in wood that have been defibrated to an average fiber diameter of several nanometers to several tens of nanometers. Cellulose defibration is mainly performed by mechanical processing, but there are also other methods, such as chemical processing to add various functional groups and mechanical processing to suppress the aggregation of cellulose nanofibers, down to the finer single nanometer level.

[0026] In the present invention, it is preferable to use cellulose nanofibers whose surface tension of a 1 wt% aqueous solution of cellulose nanofibers is 60 mN / m or less. Examples of such cellulose nanofibers include cellulose nanofibers that are defibrated only by mechanical treatment without chemical treatment and have amphiphilicity. By not chemically treating the cellulose nanofibers and not having carboxylates or carboxylic acids, the dispersion state of the cellulose nanofibers in the rubber is improved, and the tensile stress of the resulting vulcanized rubber is improved and the handling properties are also improved. Therefore, it is preferable to use cellulose that does not contain carboxylates or carboxylic acids. Amphiphilicity means that the cellulose nanofibers have both a hydrophilic part with a high affinity for water and a hydrophobic part with a low affinity for water, and as described in Patent Publication No. 5419120, it can be obtained by colliding water-suspended samples at high speed against each other. By having amphiphilicity, the affinity between the hydrophobic rubber and cellulose is increased, and a large improvement in tensile stress can be obtained with a smaller amount of mixture. In general, the surface tension of pure water is about 72 mN / m, but the greater the hydrophobicity, the smaller the surface tension. If the aqueous solution of cellulose nanofibers has a concentration of 1 wt% and a strength of 60 mN / m or less, it will have amphiphilic properties and will have a high affinity with rubber.

[0027] In the rubber composition according to one embodiment of the present invention, the content of the cellulose nanofiber is 1.2 to 3.0 parts by weight, and preferably 1.5 to 2.5 parts by weight, based on 100 parts by weight of the chloroprene rubber. By setting the content of the cellulose nanofiber to 1.2 parts by weight or more, a high tensile stress relative to the hardness can be obtained. Furthermore, by setting the content of the cellulose nanofiber to 3.0 parts by weight or less, the handling property during mixing with the cellulose nanofiber is improved.

[0028] The rubber composition can be obtained by mixing a water dispersion of cellulose nanofibers with a latex of chloroprene rubber to prepare a cellulose nanofiber-dispersed rubber latex mixture, and then removing water therefrom.

[0029] Chloroprene rubber latex is a material in which chloroprene rubber is emulsified and dispersed with an alkali metal salt of a carboxylic acid, and its production method is not particularly limited. For example, a reaction liquid obtained by emulsion polymerization of a chloroprene monomer or a monomer copolymerizable with a chloroprene monomer, or a liquid obtained by dissolving chloroprene rubber in a solvent and then emulsifying and dispersing it with an alkali metal salt of a carboxylic acid can be used.

[0030] Aqueous dispersions of cellulose nanofibers are made by mechanically defibrating wood, pulp, etc. to a specified fiber diameter and length.

[0031] The rubber composition can be produced by mixing an aqueous dispersion of cellulose nanofibers with chloroprene rubber latex to prepare a cellulose nanofiber-dispersed rubber latex mixture, removing water from the chloroprene rubber, washing with water, and then drying.

[0032] There are no particular limitations on the method for mixing the chloroprene rubber latex and the aqueous dispersion of cellulose nanofibers, and the mixture can be obtained by using a propeller-type stirring device, a homomixer, a high-pressure homogenizer, or the like, and mixing the chloroprene latex and the aqueous dispersion of cellulose nanofibers until they appear uniform (no lumps, etc.).

[0033] Methods for removing water (drying methods) from the cellulose nanofiber-dispersed rubber latex mixture include heat drying, coagulation with acid or salt, and freeze drying, but since the emulsifier, coagulation liquid, and water remain inside the rubber, making drying difficult, the freeze drying method, in which the rubber is precipitated (freeze-coagulated) by freezing, the excess emulsifier, etc. is washed away with water, and then the mixture is dried with hot air, is the most efficient and easiest method for drying. Furthermore, it is even more preferable to freeze-dry the cellulose nanofiber-dispersed rubber latex mixture at a pH of 10 or less so that the rubber can be easily precipitated.

[0034] In the method of freezing and coagulating the cellulose nanofiber-dispersed rubber latex mixture and drying it, the viscosity of the cellulose nanofiber-dispersed rubber latex mixture is preferably 1000 mPa s or less, and more preferably 600 mPa or less. If the viscosity exceeds 1000 mPa s, compatibility with current manufacturing equipment will be significantly reduced, making it difficult to obtain a rubber composition.

[0035] The obtained cellulose nanofiber-containing rubber composition can be mixed with various compounding ingredients and heated to form a vulcanized rubber, in the same manner as for ordinary chloroprene rubber.

[0036] The obtained vulcanized rubber exhibits excellent tensile stress with low strain, and the 100% tensile stress increases significantly with the amount of cellulose nanofiber added. In particular, if the 100% tensile stress increases by 1.5 MPa or more with the addition of 1 part by weight of cellulose nanofiber, the 100% tensile stress can be increased while suppressing hardness.

[0037] The increase in 100% tensile stress (M100) of a vulcanized sheet obtained by vulcanizing a rubber composition is calculated by subtracting the M100 value of a vulcanized sheet that does not contain cellulose nanofiber from the M100 value of a vulcanized sheet that contains cellulose nanofiber, and then dividing by the amount of cellulose nanofiber contained to obtain the increase in M100 per part by weight of cellulose nanofiber. EXAMPLES

[0038] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0039] <Preparation of mercaptan modified chloroprene rubber latex> The monomer mixture was mixed and stirred with an emulsified aqueous solution containing 3.5 parts by weight of potassium rosinate, 0.7 parts by weight of the sodium salt of the condensation product of naphthalenesulfonic acid and formaldehyde, 0.25 parts by weight of sodium hydroxide, 0.2 parts by weight of n-dodecyl mercaptan, and 90 parts by weight of water, and the mixture was polymerized by adding a polymerization catalyst consisting of 0.04 parts by weight of potassium persulfate and 5 parts by weight of water at a constant speed using a pump. The polymerization was carried out by adding the polymerization catalyst until the polymerization conversion rate reached 70%, and the polymerization was stopped by adding a polymerization terminator consisting of 0.01 parts by weight of t-butylcatechol, 0.02 parts by weight of sodium dodecylbenzenesulfonate, 0.5 parts by weight of chloroprene, and 0.5 parts by weight of water. Unreacted chloroprene was removed and recovered by steam stripping under reduced pressure to obtain a mercaptan-modified chloroprene rubber latex.

[0040] <Preparation of cellulose nanofiber-containing rubber composition> A specific amount of cellulose nanofiber aqueous dispersion was added to chloroprene rubber latex and mixed for 10 minutes at 2,000 rpm with an auto homogenizer (PRIMIX, manufactured by Primix Corporation) to prepare a cellulose nanofiber-dispersed rubber latex mixture. The pH was then adjusted to 6.5 with 15% by weight dilute acetic acid, and the polymer was precipitated by freeze coagulation, washed with water, and then dried with hot air.

[0041] <Surface tension measurement> The surface tension of the cellulose nanofiber aqueous dispersion was measured using a surface tensiometer (DY-300, manufactured by Kyowa Interface Science Co., Ltd.).

[0042] <Viscosity measurement> The viscosity of the cellulose nanofiber dispersion was measured using a Vismetron viscometer (Shibaura Semtec Corp.: VD2).

[0043] <Measurement of cellulose nanofiber content> The cellulose nanofiber-containing rubber composition was dissolved in 200 times the amount of chloroform for 24 hours to remove the chloroprene rubber. The solution was filtered through a 100 mesh wire screen and dried with hot air in an oven at 100°C to obtain cellulose nanofibers. The weight was measured to calculate the amount of cellulose nanofibers contained in the chloroprene rubber composition.

[0044] <Preparation of rubber compound> To 100 parts by weight of the chloroprene rubber component of the cellulose nanofiber-containing chloroprene rubber composition, 40 parts by weight of carbon black (Tokai Carbon Co., Ltd.: Seest SO), 4 parts by weight of magnesium oxide (Kyowa Chemical Industry Co., Ltd.: Kyowamag 150), 0.5 parts by weight of stearic acid (NOF Corporation: Beads Camellia Stearate), 1 part by weight of antioxidant (Ouchi Shinko Chemical Industry Co., Ltd.: Sunnock), 15 parts by weight of plasticizer (Nippon San Oil Co., Ltd.: Sansen 415), 5 parts by weight of zinc oxide (Sakai Chemical Industry Co., Ltd.: Type 2), and 1 part by weight of ethylene thiourea (Sansera 22-C) (Sanshin Chemical Industry Co., Ltd.) were added using an open roll kneader to obtain a cellulose nanofiber-containing chloroprene rubber compound. <Preparation of vulcanized material> The resulting rubber compound was press-vulcanized at 160°C for 15 minutes to prepare a vulcanized sheet.

[0045] <Hardness measurement of vulcanized material> The hardness of the obtained vulcanized sheet was evaluated according to JIS K6253 (2012). Type A was selected as the durometer.

[0046] <Measurement of mechanical properties of vulcanized products> The 100% tensile stress (M100) of the obtained vulcanized sheet was evaluated according to JIS-K-6251 (2012 edition) at a tensile speed of 500 mm / min and 23°C.

[0047] Example 1 Nanoforest S manufactured by Chuetsu Pulp Industries Co., Ltd. was used as the cellulose nanofiber, and 2.0 parts by weight of cellulose nanofiber was mixed into chloroprene rubber latex for every 100 parts by weight of chloroprene rubber (solid equivalent), and the mixture was stirred for 10 minutes using the method described above to obtain a cellulose nanofiber-containing rubber latex dispersion. The viscosity of the dispersion was 540 mPa s, which made handling easy, and a rubber composition was obtained by freeze-drying. Nanoforest S is an amphiphilic cellulose nanofiber produced by mechanical fiberization, and the surface tension of the cellulose nanofiber aqueous dispersion at 1 wt% was 55 mN / m.

[0048] A vulcanizate was made from this rubber composition according to the above method, and the hardness and 100% tensile stress (M100) were measured. The results are shown in Table 1. As can be seen from Table 1, the hardness was 73, the M100 was 7.3 MPa, so the increase in M100 was 3.8 MPa, and the cellulose nanofiber content was 2.0 parts by weight, so the increase in M100 per part by weight of cellulose nanofiber was 1.9 MPa / part by weight, which was a good result with a high M100 value relative to the hardness.

[0049] Example 2 A cellulose nanofiber-containing rubber latex dispersion was obtained in the same manner as in Example 1, except that the amount of cellulose nanofiber mixed was 2.8 parts by weight per 100 parts by weight of chloroprene rubber calculated as a solid. The viscosity of the dispersion was 870 mPa·s, which made handling easy, and a rubber composition was obtained by freeze-drying. A vulcanizate was produced from this rubber composition, and hardness and M100 were measured. As in Example 1, the increase in M100 per part by weight of cellulose nanofiber was 1.9 MPa / part by weight, and the M100 value relative to hardness was high, resulting in good results.

[0050] Example 3 A cellulose nanofiber-containing rubber latex dispersion was obtained in the same manner as in Example 1, except that the amount of cellulose nanofiber mixed was 1.5 parts by weight per 100 parts by weight of chloroprene rubber calculated as a solid. The viscosity of the dispersion was 340 mPa·s, which made handling easy, and a rubber composition was obtained by freeze-drying. A vulcanizate was produced from this rubber composition, and hardness and M100 were measured. As in Example 1, the increase in M100 per part by weight of cellulose nanofiber was 1.8 MPa / part by weight, and the M100 value relative to hardness was high, resulting in good results.

[0051] Comparative Example 1 A rubber composition and a vulcanizate were prepared in the same manner as in Example 1, except that the cellulose nanofibers were not mixed in, and the hardness and M100 were measured. Both the hardness and M100 were low.

[0052] Comparative Example 2 A cellulose nanofiber-containing rubber latex dispersion was obtained in the same manner as in Example 1, except that the amount of cellulose nanofiber mixed was 0.9 parts by weight per 100 parts by weight of chloroprene rubber calculated as a solid. The viscosity of the dispersion was 210 mPa s, which made handling easy, and a rubber composition was obtained by freeze-drying. A vulcanizate was produced from this rubber composition, and hardness and M100 were measured. The increase in M100 per part by weight of cellulose nanofiber and the M100 value relative to hardness were both low.

[0053] Comparative Example 3 A cellulose nanofiber-containing rubber latex dispersion was obtained in the same manner as in Example 1, except that the amount of cellulose nanofiber mixed was 3.5 parts by weight per 100 parts by weight of chloroprene rubber (solid weight equivalent). However, the viscosity of the dispersion was 1210 mPa s and the handleability was poor, so a rubber composition could not be obtained.

[0054] Comparative Example 4 A cellulose nanofiber-dispersed rubber latex liquid was obtained in the same manner as in Example 1, except that the cellulose nanofiber used was KY-100G manufactured by Daicel FineChem Co., Ltd. KY-100G is a hydrophilic cellulose nanofiber manufactured by mechanical fiberization means, and the surface tension of the cellulose nanofiber water dispersion at 1 wt% was 70 mN / m. The viscosity of the dispersion was 390 mPa·s, which made handling easy, and a rubber composition was obtained by freeze-drying. A vulcanizate was produced from this rubber composition, and hardness and M100 were measured. The increase in M100 per part by weight of cellulose nanofiber and the M100 value relative to hardness were both low.

[0055] [Table 1]

Claims

1. 1.2 to 3.0 parts by weight of cellulose nanofiber per 100 parts by weight of chloroprene rubber The rubber composition is characterized in that the cellulose nanofiber is amphiphilic, the surface tension of a 1 wt % aqueous solution is 60 mN / m or less, and the increase in 100% tensile stress (M100) of a vulcanized sheet obtained by vulcanizing the rubber composition is 1.5 MPa / part by weight or more relative to the amount of cellulose nanofiber added. The increase in M100 was greater than that of the vulcanized sheet containing cellulose nanofibers. The M100 value of the vulcanized sheet not containing cellulose nanofiber was subtracted from the value, and the It is calculated by dividing the amount of cellulose nanofiber contained in the sample by the amount of cellulose nanofiber contained in the sample.

2. The cellulose nanofiber is free of carboxylates and carboxylic acids and is mechanically treated. The rubber composition according to claim 1, characterized in that it is defibrated by pressing.

3. A water dispersion of cellulose nanofiber is mixed into chloroprene rubber latex to produce cellulose nanofiber. After preparing a rubber latex mixture containing dispersed nanofibers, the chloroprene rubber was frozen and solidified.

3. The method for producing a rubber composition according to claim 1, further comprising washing with water and then drying.

4. The viscosity of the cellulose nanofiber-dispersed rubber latex mixture is 1000 mPa·s or more.

4. The method for producing a rubber composition according to claim 3, wherein the rubber composition is

Citation Information

Patent Citations

  • Masterbatch of rubber / short fiber, manufacturing method for the same and pneumatic tire using the same

    JP2006206864A

  • Rubber composition and method for producing the same

    JP2009191197A

  • Rubber composition and method for producing the same

    JP2009191198A

  • Rubber composition and manufacturing method therefor

    JP2019104896A

  • Rubber composition and transmission belt using same

    WO2018056055A1